Impact of Cultural Differences on Knowledge Transfer in British, Hungarian and Polish Enterprises - Aleksandra Hauke (Fondazione Eni Enrico Mattei (FEEM), 2006)
The aim of the article is to verify the hypothesis, that despite the cultural differences existing among Great Britain, Hungary and Poland, all enterprises put much effort to ensure good conditions for knowledge sharing by their employees. It consists of two major parts. In the first one, the theoretical concepts of culture and knowledge are presented. In the second part, the interpretation of results obtained in research on macro and micro level analyses in three European countries are shown. The macro level analysis is based on the differences in cultural dimensions presented by G. Hofstede and R. Gestland while the micro level analysis is conducted based on the results of empirical investigation carried out by International Research Group: Marketing in the XXI century, among companies operating in Great Britain, Hungary and Poland. Results obtained through this survey are compared with cultural dimensions in order to see how significant the distance between the received theory and empirical investigation is.
Keywords: L10; 330; Cultural Differences; Knowledge Transfer; Wissenstransfer; Kultur; Vergleich; Ungarn; Großbritannien; Polen